Cultural Practices in Relation to the Utilization and Conservation of the Señora River and Other Community Practices - Mansueto, Josel B.; Duran, Expedita O.; Jumawan, Ricky C. (Silliman Journal, 2022)
This research investigated people’s cultural practices related to the river. Data were gathered using a Focused Group Discussion to supplement the responses to the questionnaires and actual site observations including interviews and visits. It was found out that both religious (mainly Roman Catholicism) and cultural beliefs are practiced interchangeably by the local people. Local culture and practices have contributed to the respect and realization of the limitations of the natural resources. People used indigenous ways of healing practices using plants from the riparian area of the river.